2009
DOI: 10.1007/s00402-009-0999-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of limb rotation on radiographic alignment in total knee arthroplasties

Abstract: Limb rotation had a highly statistically significant effect on measured anatomic alignment and mechanical angles. A correlation between limb rotation, anatomic mechanical angle, mechanical angles measured at femur and tibia and the femoral component distance ratio was established. As the anatomic mechanical angle and the femoral component distance ratio change linearly in the range of 20 degrees internal and external limb rotation, a calculation of the femoral component distance ratio could be used to re-calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
93
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(98 citation statements)
references
References 17 publications
0
93
0
2
Order By: Relevance
“…For example, Major et al, (1996) and Yoon et al, (2002) identified the effect of head orientation on cephalometric measurements in posteroanterior radiographs in humans. Also, Lonner et al, (1996) and Radtke et al, (2010) investigated the effect of limb rotation on the radiographic alignment of total knee arthroplasties on synthetic femur and tibia (Sawbones) for human study purposes. These studies identified an acceptable range of object rotation through which the parameters did not demonstrate significant errors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Major et al, (1996) and Yoon et al, (2002) identified the effect of head orientation on cephalometric measurements in posteroanterior radiographs in humans. Also, Lonner et al, (1996) and Radtke et al, (2010) investigated the effect of limb rotation on the radiographic alignment of total knee arthroplasties on synthetic femur and tibia (Sawbones) for human study purposes. These studies identified an acceptable range of object rotation through which the parameters did not demonstrate significant errors.…”
Section: Introductionmentioning
confidence: 99%
“…These studies identified an acceptable range of object rotation through which the parameters did not demonstrate significant errors. Furthermore, some of the studies included equations to recalculate measurements on the rotated radiographs in order to reduce the requirement to repeat radiographs (Radtke et al, 2010). In equine carpal radiography, a few parameters were established using DP views by a number of authors such as Fretz (1980), Pharr and Fretz (1981), Auer et al, (1982) and Bertone et al, (1985).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, 2D and 3D measurements on biplanar radiographs (BPR) in a weight-bearing position are well established for evaluation of degenerative, traumatic, or developmental anomalies of the lower limbs. They are part of the preoperative planning and postoperative assessment of derotational osteotomies, total knee or hip replacement, and for documentation of treatment success [6][7][8]. Preoperative assessment of lower leg length is especially important in patients undergoing total hip arthroplasty (THA), since leg length discrepancy following total hip arthroplasty is a leading cause of patient dissatisfaction, and should be corrected for a better clinical outcome after THA [9].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, while the importance of obtaining full-length, standing radiographs in assessing coronal alignment has previously been emphasized, (18, 19), two-dimensional (2D), plain radiography is also limited. Rotational attitudes due to the degree of deformity or anatomic variations such as femoral bowing, can affect standard measurements of limb alignment on 2D images (20, 21). While computed tomography (CT) scans allow 3D adjustments for limb rotation, they are obtained without weight-bearing, are time consuming, and impractical to routinely apply to clinical practice due to the high level of radiation exposure (22).…”
Section: Introductionmentioning
confidence: 99%